Working from home after COVID-19: Firms expect a persistent and intensive shift - Daniel Erdsiek; Vincent Rost (ZEW - Leibniz Centre for European Economic Research, 2022)
This study exploits fine-grained survey data to elicit firms' long-term expectations about the use of working from home (WFH) arrangements after the COVID-19 pandemic. From December 2021 until January 2022, the representative survey was conducted among more than 1,000 managers from the manufacturing industry and the information economy, which includes the ICT sector, media service providers and knowledge-intensive service providers. Firms were asked about their previous use and expected use of five different hybrid and fully remote working models ranging from 1 to 5 WFH days per week. For each model, firms indicated the share of employees who had been using this schedule before the pandemic and the share of employees who are expected to use this schedule after COVID-19.
Keywords: 330; Telearbeit; Branche; Coronavirus; Welt